PENGETAHUAN KADER MENINGKATKAN MOTIVASI DALAM MELAKUKAN DETEKSI DINI TUMBUH KEMBANG BALITA - Aticeh Aticeh; Maryanah Maryanah; Sri Sukamti (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Nurturing the qualified and comprehensive child growth development is held through theactivities of stimulations, early detection and interventions of growth development (SEDIGD)during the critical period since 1988. Government has supported the implementation ofSEDIGD for the Health Manpower in Public Health Center (Puskesmas) through training.However the research in 2013 found that there was no early detection and stimulation tothe babies visited the Integrated Care Center (Posyandu) in Administrative Village (Kelurahan)of Kayu Putih. What factors had affected thenon-implemented ofSEDIGDinKelurahan KayuPutih? The purpose of this research is to identify the determinants of motivation for theimplementation of SEDIGD to toddlers by cadres of the Integrated Care Center (Posyandu)in Kelurahan Kayu Putih in 2014. This research used cross sectional design. The sampleswere all the 101 cadres of the Integrated Care Center (Posyandu) in Kelurahan Kayu Putih.The data were analyzed using chi square with the analysis of univariate and bivariate.Result of the research showed that variables related to themotivationof early detectionofgrowth and developmentbycadreswere age(p <0,001, OR=4,6), education(p ==0,043,OR=2,72), knowledge(p =0.001, OR= 5,29). Conclusion:knowledgedeterminedthe cadres'motivationin implementingearly detectionandstimulation ofchild growth developmentinIntegrated Care Center (Posyandu).